Pengaruh Gaya Kepemimpinan Dan Motivasi Kerja Terhadap Kepuasan Kerja Karyawan (Studi Kasus Pada PT Inovasi Teknologi) - Happy Darmawan (Fakultas Ekonom dan Bisnis, Universitas Tarumanagara, 2016)
The purpose of this study was to identify and analyze the influence of motivation, leadership style and job satisfaction of employees at PT Technological Innovation. This research was conducted by simple sampling technique, with a sample of 75 respondents. The entire multiple regression equation used meets the requirements of the classical assumption test. The results of this study indicate that there is a significant and positive influence between leadership style and motivation simultaneously on employee job satisfaction in PT Technological Innovation.